Dismantling Gender Stereotypes on 'Sexual Dysfunction': Sara Mills' View in Ricis-Ryan Divorce Case - 'Athiyyah, Avita Aniqotul; Rifqi, Naflah (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 4 No 1 (2024): Proceeding of International Conference on Engineering, Technology, and Social Science 2024, 2025)
This study aims to analyze the representation of gender in the media and examine public responses to the divorce case between Ria Ricis and Teuku Ryan regarding the issue of "sexual dysfunction" through the lens of Sara Mills' critical discourse analysis. The research employs a qualitative, descriptive approach by analyzing the issue in the divorce case of Ria Ricis and Teuku Ryan concerning "sexual dysfunction." The data collection techniques used are observation and note-taking. The data analysis techniques include data reduction, data presentation, and drawing conclusions. The primary data source is a news report on the divorce case of Ria Ricis and Teuku Ryan related to the "sexual dysfunction" issue on Lesfa Channel’s YouTube video titled  “Dokter Boyke Permalukan Ria Ricis Setelah Lancang Katakan Teuku Ryan Lemah Syahwat”  [Dr. Boyke Embarrasses Ria Ricis After Rashly Claiming Teuku Ryan Has Sexual Dysfunction] published on May 7, 2024. Meanwhile, the secondary data sources consist of previous relevant studies. The results of this study show that media discourse about the divorce of Ria Ricis and Teuku Ryan portrays Ryan as an active subject revealing the pressures of their marriage, while Ricis is often depicted as a demanding object. This reflects patriarchal power and gender bias in public commentary, which tends to blame Ricis and support Ryan, reinforcing traditional norms regarding gender roles in society. Sara Mills' concept illustrates how media discourse can either reinforce or challenge power structures and social ideologies. Future researchers are encouraged to examine gender-related issues more thoroughly using diverse and engaging methods.